THERAPEUTIC POTENCY OF GREEN TEA EXTRACT ON NEUROCHEMICAL AND OXIDATIVE CHANGES CORRELATES TO AUTISTIC DISORDER IN RAT PUPS MODEL. - FATMA ELZAHRAA H. SALEM, (International Journal of Pharma and Bio Sciences, 2015)
Prenatal exposure to valproate is capable of inducing experimental autism in rat pups. This study aimed to investigate the role of green tea extract in ameliorating the toxicity induced by autism. Pregnant rats were treated with a single intraperitoneal dose of sodium valproate (600mg/kg) on 12.5thgestational day. The treatment with green tea extract started orally in autistic rat pups at postnatal day 15 for 20 days (300mg/kg). Induction of autism resulted in a significant decrease in cerebellum and cortical 5-HT, DA, NE, GABA, glycine and taurine and decrease in brain cholesterol and glutathione at P<0.05. However, it showed significant increase in glutamate, aspartate, serine and lipid peroxidation. Treatment with green tea extract showed significant improvement in most of the studied parameters at P<0.05. In conclusion, it could be stated that green tea extract exerts ameliorative effect on autistic rat pups possibly due to antioxidant action and could be effective in the management of autism.